Tinjauan terhadap Fungsi dan Faktor-faktor yang Mempengaruhi Intermediasi Perbankan Nasional - Irwan, Lella N Q (Jurnal Trikonomika, 2010)
Intermediation function of bank illustrated by numbers in credit amounts comparison that are distributed to people by third-party funds gathered by banking institutions, known as Loan to Deposit Ratio (LDR), is affected by many factors are influenced by numerous factors, both from internal and external the Bank. Among those factors, this research limits the discussion to 3 (three) factors. This research is intended to discover intermediation function of national bank and the influence of Non Performing Loan (NPL), interest rates, and Gross Domestic Product (GDP) to its intermediation function of bank. This research is intended results suggest that intermediation function of bank in Indonesia during the period of research is not optimal and the results are somewhat relatively low. Whereas, the regression results demonstrate that Gross Domestic Product (GDP) positively and significantly affects Loan to Deposit Ratio (LDR). In addition, while Non Performing Loan (NPL) can lower Loan to Deposit Ratio (LDR), its influence is not significant enough and interest rates of mortgage can barely decrease Loan Deposit to Ratio (LDR).